32 Mavacamten eligibility in patients with hypertrophic cardiomyopathy attending cardiology clinic in essex, uk. (6th June 2022) - Vara, Sarina; Dungu, Jason; Savage, Henry Oluwasefunmi; Li, Brian
Abstract : Introduction: Hypertrophic cardiomyopathy (HCM) is a heart muscle disease with few targeted therapies. Patients with left ventricular outflow tract obstruction (HOCM) are at risk of sudden cardiac death and may experience symptoms of dyspnoea, fatigue, dizziness and palpitations. As a result, the burden of symptoms often has a significantly detrimental effect on activities of daily living, exercise tolerance and subsequently results in a reduction in quality of life. HOCM patients have been treated historically with limited medical therapy options (beta-blockers and/or calcium channel blockers or Disopyramide) before proceeding to high-risk invasive treatments (alcohol septal ablation or myomectomy). There is a substantial unmet need in HCM for specific treatments to reduce obstruction and improve other parameters of left ventricular function. Mavacamten, a first-in-class, small molecule, selective allosteric inhibitor of cardiac myosin ATPase, is a new treatment for HOCM, but not routinely available in the UK pending marketing authorisation expected in Q4 2022. Methods: In anticipation of a dedicated Inherited Cardiac Conditions service for the Essex region, patients attending a general cardiology clinic with HCM were screened, to determine potential eligibility for Mavacamten. Criteria described in the double-blind, randomised multicentre Phase 3 EXPLORER-HCM study were analysed: symptomatic New York Heart Association (NYHA) class II and III; LVEF 3 55%; and Left Ventricular Outflow Tract (LVOT) peak gradient 3 50 mmHg at rest or with provocation. Results: A total of 92 HCM patients were identified, with median follow up period 52 months, median age 56 years (range 15–86), and male sex in 64%. Twelve patients had an implantable cardioverter defibrillator (ICD, 13%), 3 patients had a dual chamber pacemaker (3%) and 1 patient underwent surgical myomectomy. Maximum wall thickness (MWT) ranged from 1.2cm to 3.3cm with median LVOT gradient 9 mmHg (IQR 5–21, maximum 135 mmHg). Thirteen patients (14%) met eligibility criteria for Mavacamten and of these 62% were on a beta-blocker and 15% were on Disopyramide. Mavacamten eligible HCM patients were of similar age to ineligible patients (median 56 years for both groups, p= 0.862), with similar wall thickness (median 1.7cm for both groups, p = 0.373) and LVEF (67% vs 66%, p = 0.471), but had significantly higher LVOT gradient (median 71 mmHg vs 7 mmHg, p <0.001) and worse symptoms (92% vs 34% NYHA class 2/3, p = 0.034). Despite this, there was similar survival (p = 0.57), with a trend towards better survival in Mavacamten eligible patients compared to Mavacamten ineligible patients under proposed criteria (Figure 1). Conclusion: Treatment options for HCM are limited; the cardiac myosin inhibitor Mavacamten is an exciting new therapy, but it is currently unavailable in the UK. A small minority of our HCM patients meet the proposed criteria for Mavacamten, and within our cohort these patients do not have significantly reduced survival on current therapy. Given the mechanism of action of Mavacamten, further studies in all HCM patients, with or without obstructive physiology, are needed to expand potential licensing indications. Conflict of Interest: None to declare